Comparing Indonesian and English Proverb to Strengthen the Students’ Global Diversity (Kebhinekaan Global) - Giyatmi; Sihindun Arumi; Ratih Wijayava (PT FORMOSA CENDEKIA GLOBAL, 2024)
Profil Pelajar Pancasila is educational policies from elementary school to university to realize pelajar Pancasila. This study aims at describing how the implementation of English learning by comparing English with Indonesian proverbs and how comparing two proverbs can strengthen especially Global Diversity. This research is a descriptive qualitative research with research subjects of students majoring in Civil Engineering. The data are the results of observations and questionnaires. To collect the data, the writers used observation, documentation, and questionnaire. The writers provided game links and worksheets related to proverbs in the class. The results of the questionnaire show that comparing English and Indonesian proverbs increases their knowledge, foster mutual respect between two different cultures, and increase pride in Indonesian culture.